2023
DOI: 10.3390/nano13182578
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation Study of Calcium-Silicate-Hydrate Gel via Molecular Dynamics Simulations

Hang Yin,
Xuefeng Wang,
Haifeng Qin
et al.

Abstract: The mechanical properties of calcium-silicate-hydrate (C-S-H) gels in cementitious materials are mainly realized by nanoindentation experiments. There is limited research on the dynamic response of the molecular structure of C-S-H under nanoindentation conditions. This study simulated the nanoindentation on the C-S-H gel samples by the molecular dynamics method considering the essential factors of modeling and loading process. The results demonstrate that the averaged elastic moduli we obtained had slight diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
2
0
0
Order By: Relevance
“…Moreover, the interior of the CSH bulk displays a distinct layer-like structure with periodic density fluctuations. This layered structural characteristic of the CSH molecular model has also been observed in numerous previous studies, corroborating our experimental findings [31,33]. Notably, these studies have identified the regions where water molecules tend to aggregate during the stretching of CSH alone and its involvement in composite structures as potential fracture sites [18,38].…”
Section: Density Profilesupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the interior of the CSH bulk displays a distinct layer-like structure with periodic density fluctuations. This layered structural characteristic of the CSH molecular model has also been observed in numerous previous studies, corroborating our experimental findings [31,33]. Notably, these studies have identified the regions where water molecules tend to aggregate during the stretching of CSH alone and its involvement in composite structures as potential fracture sites [18,38].…”
Section: Density Profilesupporting
confidence: 92%
“…The Q n distributions of the silicate chains in the CSH molecule used in this paper were Q 0 = 9.4%, Q 1 = 68.2% and Q 2 = 22.4%, which are close to the distributions of the experimental samples (Q 0 = 10%, Q 1 = 67%, Q 2 = 23%) [32]. Furthermore, the influence of the oxhydryl (-OH) group on the mechanical properties of CSH was not taken into account here due to its limited effect [33]. The saturated C-S-H structure exhibits the chemical formula of (CaO) 1.69 (SiO 2 )•1.81H 2 O, which closely resembles the composition (CaO) 1.7 (SiO 2 )•1.8H 2 O obtained through the small-angle neutron scattering (SANS) test [34].…”
Section: Simulation Modelsupporting
confidence: 71%